Characterization of the Divergent sacBK and sacAR Operons, Involved in Sucrose Utilization by Lactococcus lactis - Luesink, Evert J. (American Society for Microbiology, 1999)
The divergently transcribed sacBK and sacAR operons, which are involved in the utilization of sucrose by Lactococcus lactis NZ9800, were examined by transcriptional and gene inactivation studies. Northern analyses of RNA isolated from cells grown at the expense of different carbon sources revealed three sucrose-inducible transcripts: one of 3.2 kb containing sacB and sacK, a second of 3.4 kb containing sacA and sacR, and a third of 1.8 kb containing only sacR. The inactivation of the sacR gene by replacement recombination resulted in the constitutive transcription of the sacBK and sacAR operons in the presence of different carbon sources, indicating that SacR acts as a repressor of transcription.